PENGARUH BRAND AWARENESS TERHADAP BRAND LOYALTY DENGAN BRAND ASSOCIATION DAN PERCEIVED QUALITY SEBAGAI VARIABEL MEDIASI (Studi Pada Pengunjung Mall Malang Town Square) - MUHAMMAD MAULANA AULIA ; Ananda Sabil Hussein, SE., M.Com., Ph.D
This research based on phenomenon about shopping centers competition that_x000D_ grows in Malang City. Marketers are required in order to convey a message to_x000D_ consumers to build brand equity. This research aims to know the influence of_x000D_ brand equity variable, which consist of brand awareness, brand association, and_x000D_ perceived quality on brand loyalty either directly or indirectly at Malang Town_x000D_ Square’s visitors. _x000D_ Type of this research is explanatory research with survey method. Total _x000D_ sample are 160 respondents with purposive sampling technique. Analysis method _x000D_ uses PLS SEM with SmartPLS 3.0 software. Instrument tests including outer_x000D_ model test, inner model test, and hypothesis test. Direct hypothesis test uses t-test,_x000D_ while indirect hypothesis test uses sobel test. _x000D_ The result of analysis show that brand awareness influences positively and_x000D_ significantly on brand association, perceived quality, and brand loyalty._x000D_ Perceived quality also influences positively and significantly on brand loyalty._x000D_ But, brand association not gives significant influence on brand loyalty. _x000D_ Meanwhile if through indirect influence, perceived quality can positively and_x000D_ significantly intervene the influence of brand awareness on brand loyalty. _x000D_ However, brand association cannot give significant effect for intervene the_x000D_ influence of brand awareness on brand loyalty. _x000D_ _x000D_ Keywords: Brand Equity, Brand Awareness, Brand Association, Perceived_x000D_ Quality, Brand Loyalty.